Feasibility of a Responsibility-Based Leadership Training Program for Novice Physical Activity Instructors - Toivonen, Hanna-Mari; Hassandra, Mary; Wright, Paul M.; Hagger, Martin S.; Hankonen, Nelli; Laine, Kaarlo; Lintunen, Taru (Frontiers in Psychology, 2021)
Most coaches and instructors want to support athletes’ or children’s holistic development and teach them to take responsibility and lead rather than only teach sport skills. To do that, they need to learn by themselves and teach their athletes or children to be autonomous, share leadership and master life skills. Toivonen et al. (2021) adapted Hellison’s Teaching Personal and Social Responsibility (TPSR) model to train novice physical activity instructors. The leadership training program taught novice physical activity instructors to promote positive youth development, personal and social responsibility, and shared leadership in a physical activity context. The aim of the current study was to evaluate the feasibility of the leadership training program (Toivonen et al., 2021) to optimize the program and to determine whether to proceed to further evaluation. The participants in the leadership training program were eight Finnish novice physical activity instructors, aged 18 to 22. They had minimal to no leadership training or experience. The training program consisted of seven meetings totaling 20 hours. The TPSR model was the theoretical and practical framework of the training program. Feasibility of the leadership training program was evaluated across four domains of an evidence-based framework: demand, practicality, acceptability, and implementation fidelity. Data of the current complex intervention were collected with questionnaires, researcher’s log, lesson plans, video recordings and a semi-structured focus group interview. The quantitative data were analyzed using descriptive statistics and the qualitative data using deductive and inductive content analysis. There was a demand for the leadership training program. The training program was perceived as practical and highly acceptable by the novice instructors and the trainers, and implemented with fidelity, indicating high overall feasibility. No implementation issues were found. Consequently, the current leadership training program has a high probability of efficacy and can be accepted for further evaluation.